Techno-economic case study: Bio-fixation of industrial emissions at an Indian oil and gas plant - Choudhary P.; Srivastava R.K. (My University, 2025)
In recent years, microalgae have been targeted for emitted carbon capture besides producing value-added products like biofuels, biogas, food supplements and other nutrients. The present work has evaluated the carbon dioxide capture potential of microalgae Chlorella sp utilizing the oil and gas industrial vent gas at an Indian gas processing complex. The vent gas CO2 is targeted for bio-fixation and algal biomass was converted into biogas with anaerobic digestion process, which substitutes the natural gas being utilized in heater treater application in the oil and gas process chain. The pilot scale carbon sequestration using two different algal cultivation methods with Chlorella sp with vent CO2 has compared, and biogas has been suggested as one of the emerging and promising solutions to mitigate climate change and supporting energy security challenges. An integrated hybrid model with algal biomass-solar-natural gas has been developed and analyzed for its techno-economic feasibility as carbon mitigation approach and utilizing solar energy for electricity and biogas based heat requirements. The average biomass productivity was found to be 186.43 kg ha1d1 and carbon sequestration quantum of 151.23 kg ha1d1. The study suggests that the productivity and quantum of algal biomass matches with biogas heat equivalent requirement for crude oil heating system and hybrid model is technically viable. The economic feasibility study is based financial modeling and recent Indian government regulations (EMRETR-2017) on the promotion of renewable energy with Renewable Purchase Obligations-2010. The study results and financial modeling derived a reasonable internal rate of return of 24% and payback time of 5.1 years, besides the carbon credits as 191 M$ and 125 $ renewable energy certificate equivalent could further reduce the rate of return and makes better environmental sustainable. © 2020 Elsevier Ltd